Analisis Persepsi Guru pada Sekolah Penggerak mengenai Projek Penguatan Profil Pelajar Pancasila sebagai Penguatan Karakter Peserta Didik - Khairunisa, Wafa; Sundawa, Dadang; Rahmat, Rahmat; Wiaratama, Muhammad Rafsan (PAKAR Pendidikan, 2024)
This research was conducted based on the importance of the program released by the new system curriculum in Indonesia, namely the Merdeka Curriculum, to overcome the crisis in the character of the nation's children in the era of globalization. This research aims to analyse the perceptions of teachers at Sekolah Penggerak regarding the Profil Pelajar Pancasila Project as a step to strengthen the character of students by considering several indicators such as process, results, and evaluation. The approach used in this research is quantitative, using descriptive methods. Data collection was carried out through the distribution of questionnaires and interviews with several informants as supporting data. The data analysis techniques used are reduction, presentation, and conclusion. The overall indicator results have reached a score of 81.9%, indicating that the implementation of this program has been successful and has achieved a high percentage in strengthening student character. Supported by informant interviews, this activity has a very positive effect, as students at school gain cognitive knowledge and can train their affective and psychomotor skills. This activity is not only a curriculum program but can help students improve their positive character at school and in the surrounding environment.